2018
DOI: 10.1186/s40104-018-0306-5
|View full text |Cite
|
Sign up to set email alerts
|

Surplus dietary isoleucine intake enhanced monounsaturated fatty acid synthesis and fat accumulation in skeletal muscle of finishing pigs

Abstract: BackgroundIsoleucine (Ile) has been implicated in the regulation of energy homeostasis and adipogenesis. However, the impact of surplus dietary Ile intake on muscle lipogenesis remains unknown. The present study aimed to investigate the impact of dietary supplementation of extra-Ile on lipogenesis, fatty acid profile and lipid accumulation in skeletal muscle in finishing pigs.MethodsForty-eight barrows with initial body weight of 77.0 ± 0.1 kg were allotted to one of two groups and fed diets containing 0.39%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 42 publications
5
31
0
Order By: Relevance
“…Feeding high fat diets with the inclusion of BCAA to rodents reduces obesity and hepatocyte fat deposition [8]. In finishing pigs, isoleucine supplementation increase lipogenesis in intramuscular fat [9]. Furthermore, BCAAs play functional roles in the female animal during lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding high fat diets with the inclusion of BCAA to rodents reduces obesity and hepatocyte fat deposition [8]. In finishing pigs, isoleucine supplementation increase lipogenesis in intramuscular fat [9]. Furthermore, BCAAs play functional roles in the female animal during lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that surplus dietary Ile, one of BCAAs, increased the IMF content in skeletal muscle via the upregulation of lipogenic genes by stimulating lipogenesis in skeletal muscle tissue of finishing pigs [ 19 ]. In the previous study, Luo et al clearly showed the effect of extra Ile in the diet on lipogenesis in the muscle tissue, serum cholesterol levels, and fatty acid composition without affecting growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, Luo et al clearly showed the effect of extra Ile in the diet on lipogenesis in the muscle tissue, serum cholesterol levels, and fatty acid composition without affecting growth performance. However, it is not possible to further discuss whether Ile (BCAA) intake into the muscle cells affected lipid synthesis due to the lack of Ile level in muscle tissue [ 19 ]. In contrast, it has been well known that BCAA are effective amino acids to regulate protein synthesis because of a greater increase in protein synthesis than degradation [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the fatty acid composition of meat has been reported to be altered due to changes in target diets during the animal production cycle [7,25,26]. Therefore, the balance between fatty acid deposition and absorption could be indicated by the variations of fatty acid profile that is detected in skeletal muscle [22]. Fatty acid composition is also an important factor that determines the nutritional value and oxidative stability of muscle [27].…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression levels of target genes were calculated using the 2 −ΔΔCt method [21]. All PCR primers used in this study are listed in Table 2 [22,23].…”
Section: Methodsmentioning
confidence: 99%